HUBUNGAN CACING TANAH DENGAN KONDISI FISIK, KIMIA DAN MIKROBIOLOGIS TANAH MASAM ULTISOL DI DAERAH LAMPUNG UTARA (Relation of Earthworm with Physic, Chemist and Microbiologic Condition of Ultisol Acid Soil in North Lampung Area) - S., Wibowo (Universitas Palangka Raya, 2016)
ABSTRAKA study has been done to know relation of earthworm with physic, chemist and microbiologiccondition of ultisol acid soil in North Lampung, Sumatera. The research indicated there was strongpositive correlation between contents of light and moderate fractions of soil organic matter and Corganikwith earthworm population. There was strong positive correlation between contents of totalfraction, light and moderate fractions of soil organic matter, C-organic and earthworm population withtheir freshweight. There was strong positive correlation between contents of total fraction, moderateand heavy fractions of soil organic matter, N-total and earthworm freshweight with sum of theircocoons. There was strong positive correlation between contents of light and moderate fractions ofsoil organic matter, C-organic, N-total and earthworm freshweight with weigth of their casts. Thepopulation, freshweight, sum of cocoons and casts weight of eartworms have positive correlation withsoil porosity. Soil temperature have negative correlation on all of variables. Sum of fungi and totalmicroorganisms have not strong correlation on the earthworms. The low of soil pH have not negativeeffect on the earthworms, it was suspected because which was lived in there were all of adaptablespecies with ultisol acid soil.Keywords : Earthworm, Physic, Chemist dan Miocrobiologic Condition, Ultisol Acid Soil